The Future of Merger What Do We Want Mergers To Do: Efficiency or Diversity? - Lang, Daniel W. (Canadian Journal of Higher Education, 2003)
Mergers have been a frequent phenomenon in higher education in the last quarter century. The conventional wisdom is that mergers are undertaken mainly for economic reasons, either to expand markets or to reduce costs. About four out of five college or university mergers survive. In the for-profit sector the comparable rate is closer to two out of five. From this one might conclude that the future for mergers among colleges and universities is robust. If, however, the principal purpose of mergers is economic efficiency, there logically ought to be a point beyond which the efficacy of merger will begin to decline. There is, however, another motive for merger, which is unrelated to economic efficiency. Mergers can produce greater diversity of programs and services, both among individual colleges and universities and within systems of postsecondary education. If diversification is the primary purpose of merger, the future might look different and might depend on new ways of identifying peers and partners for merger. This essay examines the expectations that are held for mergers, the realism of those expectations, and the means by which partners in mergers are identified and selected. It concludes with the suggestions that diversification may replace efficiency as the main stimulus of merger, and that, as the choice is made between efficiency and merger, institutions and systems of post- secondary education may try other, less permanent, forms of inter-institutional cooperation before committing to merge.